Benzimidazole compound and organic electronic device thereof - GUO HUANGMING; LAI ZHENCHANG; YAO ZHENGCONG; HUANG HELONG; ZHANG MINZHONG; LIN QIZHEN (2020)
The invention relates to a benzimidazole compound. The benzimidazole compound is represented by a formula 1 as follows, wherein L1 and L2 each is phenylene independently, and n1 and n2 each is 0, 1 or2 independently; and R1 is substituted or unsubstituted C6-30 aryl or -N(Ar1)(Ar2), and R2, R3, R4, L3, n3 and X are as defined in the description. The compound represented by the formula 1 is a bipolar subject material, has excellent current carrier transfer balance and thermal stability and can be applied to organic electronic devices. 本发明关于一种苯并咪唑化合物，系以下述式1表示：其中，L与L独立地为亚苯基，n1和n2各自独立地为0、1或2；R为经取代或未经取代之碳数6至30的芳基、-N(Ar)(Ar)、R、R、R、L、n3及X如同说明书中之定义，式1化合物为双极性主体材料，具有优异的载流子传递平衡性及热稳定性，并可用于有机电子装置。